Hubungan Manajemen Keuangan Dan Iklim Sekolah Dengan Efektivitas Sekolah Dasar Negeri Kecamatan Duren Sawit - Venny Oktaviany (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2016)
The purpose of this research is to determine the relationship financial management and school climate with school effectiveness of state elementary school in district of Duren Sawit. It was a quantitative research with a survey method. The samples were teachers of State Elementary Schools in district of Duren Sawit amounted to 230 persons selected by proportional random sampling. The data were analyzed with inferential statistics using regression and correlation analysis.The results concluded that (1) there is a positive correlation between financial management with effectiveness school; (2) there is a positive correlation between school climate with effectiveness school; (3) there is a positive correlation between financial management and school climate together have positive with effectiveness school.The purpose of this research is to determine the relationship financial management and school climate with school effectiveness of state elementary school in district of Duren Sawit. It was a quantitative research with a survey method. The samples were teachers of State Elementary Schools in district of Duren Sawit amounted to 230 persons selected by proportional random sampling. The data were analyzed with inferential statistics using regression and correlation analysis.The results concluded that (1) there is a positive correlation between financial management with effectiveness school; (2) there is a positive correlation between school climate with effectiveness school; (3) there is a positive correlation between financial management and school climate together have positive with effectiveness school.